COMBINING ABILITY FOR QUANTITATIVE TRAITS IN SESAME THROUGH LINE X TESTER ANALYSIS - MAINI BHATTACHARJEE; SABYASACHI KUNDAGRAMI; TAPASH DASGUPTA (The Bioscan, 2021)
Analysis of combining ability and genetic architecture were evaluated for twelve morphological quantitative characters in sesame using Line x Tester mating designs. The analysis of variance revealed that significant differences between lines and testers were observed for all the characters. Suprava and GT 10 found as a good general combiner for seed yield/plant and some yield component traits with early maturity. The top high yielding cross combinations viz RT 351 X TKG 22, Suprava X AT 238, Suprava X TKG 22, HT 2 X AT238, Savitri X CUHY 57 showed high, significant and positive SCA effects for yield and involved either good x good, good x poor or poor x poor combining parents. Heterosis for seed yield per plant ranged from -16.40 to 78.59, -21.98 to 18.59 and -21.35 to 33.51and -18.58 to 38.20 percent over mid parent, better parent and two standard varieties respectively. Among the hybrids Suprava X AT 238 and RT 351 X CUHY 57 were identified as the best performing hybrid. Hence the present study suggesting that these crosses could be utilized for the improvement of sesame yield and also in future breeding program for commercial exploitation.